Survey on Different types of Neural Network Techniques to Classify Human Face (International Journal of Engineering and Computer Science, 2015)
Face Detection presents a challenging problem in field of image study and computer visualization but nowadays, Face Detection is important technique because it uses in various Application. There are many approaches to implement it. In this paper, an overview of some of the well-known methods in each of these categories is provided and some of the benefits and drawbacks of the schemes mentioned are examined. This paper also mentions some of the most recent algorithms developed for this purpose and attempts to give an idea of the state of the art of face recognition technology.